TINGKAT STRESS ORANGTUA MEMPENGARUHI PERILAKU ADAPTIF ANAK RETARDASI MENTAL DI SLB BC KEPANJEN KABUPATEN MALANG. - Istafia .; Faizatur Rohmi; Ronal surya Aditya (Poltekkes Kemenkes Malang, 2020)
Parents waiting for the presence of a child can be a disappointment if the child is born experiencing mental retardation, one of which is mental retardation. Mental retardation is a disorder of intellectual function characterized by IQ below 70 and adaptive behavior disorder is an obstacle to adapt to the environment. Adaptive behavior of mentally retarded children who are different from other normal children becomes a burden for both parents, those who lack emotional control make themselves stressed because of their childrens behavior. Stress occurs more with a mother than a father, because mothers often care for their children and are closer to their children. The design of this research uses the Non Experimental method with Cross Sectional approach. The population is all respondents, namely all parents of mentally retarded children. Sampling using Total Sampling with a sample of 74 respondents. Data collection methods using the DASS 42 questionnaire were used only on the stress range of 14 questions, and used the childrens adaptive behavior questionnaire of 15 questions. The data obtained are presented in the form of frequency distribution tables and narratives. The results showed that of the 74 respondents having a severe stress level category as many as 63.5 percent with adaptive behavior of moderate children as many as 90.5 percent. The statistical test uses the Spearman Rank Test which shows the magnitude of the correlation coefficient between the two variables namely 0.837 with a significance of 0.038, which means there is a significant relationship between parental stress level and mental retardation behavior of children. The conclusion of this study is that there is a relationship that the adaptive behavior of the mentally retarded child to the level of parental stress due to the behavior of children who are different from other normal children becomes a burden for both parents. Keywords: Stress level, Adaptive Behavior, Mental Retardation.